Desenvolvimento técnico e avaliação de custo e benefício do sistema construtivo de painéis sanduíche, com núcleo de garrafas PET, moldados no local - Fernandes, Georgeo Dias (2016)
Traditional construction methods are questioned, because of low productivity, waste, rework, low standardization, among other things. Because of these problems and taking into account environmental aspects, new building systems that make use of reusable or recyclable materials from other industries are analyzed to verify its efficiency in technical and economic level. In this context, the aim of the dissertation is to describe the technical development and assess costs and benefits of the constructive system sandwich panels, molded on site, which reuses bottles of polyethylene terephthalate (PET) to make up the core of the walls and slabs. Concerning the technical development was described experiments and tests carried out for the conformation of the construction system, with the configuration of its characteristics and peculiarities, discussed the results of the tests performed, including the early to define the structural safety of the walls and slabs together with the presentation of the theoretical model calculation and performance evaluation for the validation. In the economic aspect, there was a comparison between the traditional construction system and the studied system. The cost direct was examined and observed the benefits with the help of value attributes expected to prefabricated options construction, drawn by Cook (2013), namely: direct costs (material and labor), time (schedule), design flexibility, work time management, quality, delivery and conference in work, subcontractors activities in work, work safety, exercise stress testing, health, environmental impact, LEED certification, rubble and dispensing, public relations, marketing, maintenance (life cycle). With the help of estimators engineers, through interviews, the steps we investigated, activities, productivity and resources needed to execute a project in the traditional building system, building system in masonry traditional system and building system analyzed. Was elaborated cost composition of spreadsheets and productivity for hypothetical situations of conventional and innovative construction system of sealing walls with slabs of residential buildings and walls and structural slabs works until two floors. The mapping process was designed, in which to extract the consideration of potential benefits or otherwise of the building system. Technical descriptions highlight the possibility of constructive feasibility of sandwich panels, with core of PET bottles, molded on site. And the evaluation of costs and benefits demonstrates its value, not so much due to the direct cost, but in terms of building system management benefits.